Reducing disinfection byproduct precursors through coagulation enhancement as particle weight and size control using potassium permanganate. (23rd December 2022) - Bayomi, Ahmed M.; Souaya, Eglal R.; Ismail, Eman H.; Mohamed, Gehad G.; Hussein, Mahmoud Mohamed Fouad
Abstract: The widespread use of chlorine pre-oxidation in water purification has been limited in several countries owing to the production of carcinogenic byproducts when combined with naturally occurring organic matter. This study investigates the efficient use of potassium permanganate (KMnO4 ) pretreatment and coagulation enhancement as particle size and molecular weight distribution controlling parameters. KMnO4 pretreatment significantly reduced the apparent molecular weight of humic acid due to KMnO4 reduction and the continuous generation of manganese dioxide (MnO2 ) formed in situ under neutral and alkaline conditions. The MnO2 formed in situ had adsorption characteristics that enabled it to form large and stable flocs with the hydrolysis products of aluminum sulfate. However, under acidic conditions, KMnO4 pretreatment exhibited strong oxidation characteristics due to Mn(VII) reduction to Mn(II), and the mean particle floc size was the same as without KMnO4 pretreatment. Overall, KMnO4 pretreatment is a useful alternative strategy for traditional pre-oxidation using chlorine and a good coagulant enhancement agent in neutral and basic media. HIGHLIGHTS: pH is crucial in the KMnO4 pretreatment mechanism. Under acidic conditions, KMnO4 pretreatment results in the same mean particle floc size as alum alone. The in situ formed MnO2 is incorporated with the alum hydrolysis product, forming larger flocs. KMnO4 pretreatment under optimal conditions results in a significant reduction in the molecular weight distribution of humic acid. Graphical Abstract